Taboo Language Used by Thomas Shelby in “Peaky Blinders” Tv Series - Andra Adrian Dwi Atmoko (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
This research focus on used taboo language by Thomas Shelby in Peaky Blinders Tv series. Researcher concentrates on the taboo words that happen during the conversation of Thomas Shelby in Peaky Blinders TV series. Peaky Blinders is a British TV series that is the work of Steven Knight. A colossal drama that tells the life of a mafia family in Birmingham in 1919. Led by a boss who is highly respected by his men, Thomas Shelby. A man who is described as having a calm, fierce, masculine appearance and a symbol of a real man. As well as the spirit of leadership to his gang members who are very authoritative and respected. The method used in this article is a qualitative method. Qualitative method is a research approach that aims to understand and explain social phenomena or human life by exploring non-numerical data, such as words, images, sounds, or subjective experiences. This method focuses on an in-depth understanding of the context, meaning, and perspective of individuals or groups who are the subject of research. In collecting data, researcher looks for phenomena or sources related to the theory to be discussed. Firstly, the researcher watched the phenomenon in the form of a video containing the topic discussed. Then, researcher interpret the phenomena that occur using related theories, Language and culture (Taboo). Next, the researcher counted the number of sentences spoken and the number of taboo language spoken in the conversation between Thomas Shelby and his friend. In analyzing the data, the researchers applying Battistella (2005) types of taboo word theory. The most type of taboo word uses is obscenity. The objectives of this research are to identify the types of taboo words uttered by Thomas Shelby in Peaky Blinders TV series. The show is set in Birmingham, England in the aftermath of World War I, and the use of profanity is meant to reflect the rough and gritty nature of the time period.